2021
DOI: 10.1002/ijgo.13989
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum stillbirth rates during the COVID‐19 pandemic in Austria: A population‐based study

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has had dramatic effects on the pregnant population worldwide, increasing the risk of adverse perinatal outcomes. Objective To assess the incidence of antepartum stillbirth (aSB) during the COVID‐19 pandemic in Austria. Methods We collected epidemiological data from the Austrian Birth Registry and compared the rate of aSB (i.e., fetal death at or after 24+0 gestational weeks) during the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(34 reference statements)
1
11
0
1
Order By: Relevance
“…Within the published literature, single-center 45,51,5355 and national 5660 studies have reported conflicting evidence in relation to perinatal outcomes during the COVID-19 pandemic. In a meta-analysis, Yang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the published literature, single-center 45,51,5355 and national 5660 studies have reported conflicting evidence in relation to perinatal outcomes during the COVID-19 pandemic. In a meta-analysis, Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect modification by SES was not assessed in the aforementioned studies. [19][20][21][22] Within the published literature, single-center 45,51,[53][54][55] and national [56][57][58][59][60] studies have reported conflicting evidence in relation to perinatal outcomes during the COVID-19 pandemic. In a metaanalysis, Yang et al examined the influence of COVID-19 restrictions on maternal and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the number of requests for in utero transfers because of threatened preterm birth and fetal growth restriction decreased during lockdown. Many authors have reported a significant impact of the pandemic, and more specifically, of the different lockdowns on preterm delivery rates and on low-birth-weight births [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies show a decrease in the number of preterm births during successive lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, the exact gestational age of the first-trimester miscarriages occurring before 12 completed gestational weeks was not available. Based on registrations in Denmark, the median gestational week of the registered first-trimester miscarriages was 8 weeks (interquartile range 6,9). From the Swedish Pregnancy Register, we retrieved information on all births at ≥ 22 gestational weeks during the same time period; in Sweden, 92% of births are included in the national register (18 of 21 Swedish regions).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested early on that pandemic mitigation measures could influence the rate of pregnancy outcomes; however, whether this is the case is controversial due to inconsistent findings across countries 3 . Some studies report evidence of an increase in stillbirths during the first wave of the pandemic 4 9 , while other studies found no evidence of a difference 10 17 . A meta-analysis concluded that there was significant evidence of an increase in stillbirths after pandemic lockdown 18 .…”
mentioning
confidence: 99%